A cost-efficient architecture for the campus information system based on transparent computing platform. (2016) - Guo, Kehua; Xiao, Yizhe; Duan, Guihua
This paper presents a novel architecture named CISTC for the campus information system (CIS) based on transparent computing (TC) platform, as well as the development, deployment and maintenance experiences to improve the economic efficiency. Firstly, the system architecture of CISTC is introduced. Secondly, we describe the transmission of operating systems and applications, data management and interface release. Then, the software development, deployment and maintenance processes in CISTC are described. Finally, we design some mathematical models to evaluate the economic efficiency of CISTC. The results show that using transparent computing platform as the CIS constructing environment can enhance the economic efficiency and lead to increased user experience in comparison with the traditional approach.